LITERATURE REVIEW: THE EFFECT OF PROJECT BASED LEARNING LEARNING MODELS ON STUDENT LEARNING OUTCOMES IN SCIENCE LEARNING - indah preselia putri (Department of Science Education, 2022)
This study aims to figure out the effect of the Project Based Learning model on learning outcomes of students in science learning. This research is motivated by a lot of research on the effect of project based learning on student learning outcomes. This research is an ex post facto research with descriptive data analysis. The population in this study were all articles originating from indexed journals related to the effect of project based learning on student learning outcomes. The sample used was 8 Scopus indexed articles and SINTA accredited. Based on the results of the analysis of the articles conducted, it was found that the project based learning model had a positive influence on learning outcomes seen from the cognitive, affective, and psychomotor domains in the form of increasing student creativity and junior high school student science skills in science learning.